The Influence of Skills and Responsibilities on Career Development of Regional Library, Archives, and Documents Agency Employees Parigi Moutong District - Rukhayati Rukhayati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
Career development will exist in the future that depends on human resources, so career development for employees must be carried out in a planned and sustainable manner every year. In other words, career development is one of the human resource management activities that must be carried out as a formal activity in an integrated manner with other human resource activities. Suppose an employee has the skills and is supported by high responsibility for the work given. In that case, the results of the work given by the employee will generally be good, and the leadership can consider the career development of the employee. This study aimed to determine and analyze the effect of skills and responsibilities simultaneously and partially on the career development of employees of the Regional Library, Archives, and Documents Agency of Parigi Moutong Regency. Using multiple linear regression analysis, the results obtained that skills and responsibilities simultaneously or partially significantly affect the career development of the Regional Library, Archives, and Documents Agency employees of Parigi Moutong Regency. j